CP-161 Incidence of abnormalities of urinary dipstick tests in patients receiving biotherapies. (14th February 2016) - Vandewoestyne, S; Cantagrel, A; Cestac, P; Morin, MC; Calmels, V; Civade, E
Abstract : Background: Biotherapies are mostly used in the treatment of chronic inflammatory rheumatism, such as rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis. Because they expose patients to a higher risk of infection, a urinary dipstick test (UDT) is performed in all patients who receive biotherapies. Purpose: The aim of this study was to evaluate the relevance of systematically performing a UDT in patients in the rheumatology day hospitalisation unit. Material and methods: A UDT was done for each patient during hospitalisation. When they were positive (positive nitrites and/or leukocytes strong), a cytobacteriological examination of urine (CBEU) was performed as well as a summary of clinical information. Results: 553 UDT were performed in 354 patients over 2 months. Median age of the patients was 56 years and 66% were female. From the 553 UDT performed, only 15 (3%) were positive: 10 UDT had only strong leukocytes and 5 had only positive nitrites. 3 positive UDT did not lead to a CBEU: 2 of them did not show any clinical signs and biotherapies were injected. The third patient was already septic on arrival and was receiving antibiotics. Of the 12 CBEU performed, 6 showed significant bacteriuria: 5 positive for Escherichia coli and 1 for Enterococcus faecalis . Among these 6 patients: 3 had asymptomatic bacteriuria and received their biotherapy and 3 were symptomatic. 2 patients were diagnosed with cystitis and pyelonephritis was discovered in a third patient. All were treated with an appropriate dose of ofloxacin. Only the patient with pyelonephritis did not receive biotherapy; for the other 2, the injection was delayed. Conclusion: Given the low frequency of abnormalities in the UDT, the therapeutic approach was modified in 3 cases and each time patients showed clinical signs. According to the literature, the risk of infection is higher during the first 6 months of treatment with biotherapies: 2 of the 3 patients had started their biotherapy less than a year before the onset of the urinary tract infection. Examination and clinical review should remain the primary elements in the diagnosis of a possible UTI and the therapeutic decision making. No conflict of interest.